2018
DOI: 10.1371/journal.pone.0193727
|View full text |Cite
|
Sign up to set email alerts
|

Timing of embryonic quiescence determines viability of embryos from the calanoid copepod, Acartia tonsa (Dana)

Abstract: Like 41 other calanoid copepods, Acartia tonsa, are capable of inducing embryonic quiescence when experiencing unfavorable environmental conditions. The ecdysone-signaling cascade is known to have a key function in developmental processes like embryogenesis and molting of arthropods, including copepods. We examined the role of ecdysteroid-phosphate phosphatase (EPPase), ecdysone receptor (EcR), ß fushi tarazu transcription factor 1 (ßFTZ-F1), and the ecdysteroid-regulated early gene E74 (E74), which represent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…This revealed that embryos that were entering quiescence before the gastrulation stage would stay in gastrulation during the rest of quiescence, and that they exhibited a slower pace of hatching compared to subitaneous embryos. In contrast, embryos entering quiescence after gastrulation would stay in later embryonic stages during quiescence, and they showed a rapid pace of hatching after quiescence termination (Nilsson and Hansen, 2018).…”
Section: Distinguishing Characteristics Of Resting Egg Categoriesmentioning
confidence: 96%
See 3 more Smart Citations
“…This revealed that embryos that were entering quiescence before the gastrulation stage would stay in gastrulation during the rest of quiescence, and that they exhibited a slower pace of hatching compared to subitaneous embryos. In contrast, embryos entering quiescence after gastrulation would stay in later embryonic stages during quiescence, and they showed a rapid pace of hatching after quiescence termination (Nilsson and Hansen, 2018).…”
Section: Distinguishing Characteristics Of Resting Egg Categoriesmentioning
confidence: 96%
“…5), which traits create resistant individuals that can survive periods of adversity, and how the answers to these questions relate to species distribution. Understanding of the epigenetic and genetic mechanisms underlying embryonic dormancy is also limited (Nilsson, 2017). Therefore, I ask the following questions: (1) What are the physical-chemical-biological cues (day length, light intensity, temperature, crowding stress, food shortage, etc.…”
Section: Unresolved Questions About Copepod Resting Eggsmentioning
confidence: 99%
See 2 more Smart Citations
“…RNA was extracted using the RNeasy mini Blood and Tissue kit from Qiagen (Hilden, Germany) according to protocol with the following modifications: sample tissue was kept on ice and ground in a 1.5 ml Eppendorf tube using a pestle and electric motor for two minutes and incubated with proteinase K for 4 hours with periodic mixing. The embryo RNA sample consisted of eggs from a few and up to 50 hours old to ensure that all stages in A. tonsa embryogenesis were present [45]. An overview of the libraries was constructed, and more details on indexes, insert sizes, biological materials, and SRA accession numbers can be found in Supplementary Material 1.…”
Section: Nucleic Acid Extraction Library Construction and Sequencingmentioning
confidence: 99%